Educative hyper-environment for learning the subject Methodology of the Investigation and the introduction to Inferencial Statistics for the nursing career - Alcides Muguercia Bles; José Antúnez Coca; Omara Mercedes Cardona Sánchez; Magnolia Paula Sarmiento Cardonne (Centro Provincial de Información de Ciencias Médicas, 2022)
An educative hyper-environment on the study program of the subjects Methodology of Investigation and Introduction to the Inferencial Statistics was implemented, which allowed to organize the access to updated information, and, with this, to improve the teaching-learning process. For this purpose, 10  professors and 57 students belonging to the fourth year of the nursing degree from the Health Technology-Nursing Faculty in Santiago de Cuba city were interviewed, likewise, the effectiveness level of the actions carried out with the students -under the guide of professors and tutors- aimed at improving the scientific and professional training, which was evidenced in the changes in attitude and motivation when evaluating the significance of the results, as well as in the increase in the number of participants in the scientific events and in the higher quality in the contents of the investigations.  Teachers, tutors and students evaluated the hyper-environment as adequate and it was shown that its implementation may contribute to the teaching-learning process of the Methodology of Investigations and of the introduction to Inferencial Statistics.